2010
DOI: 10.1158/1535-7163.mct-10-0167
|View full text |Cite
|
Sign up to set email alerts
|

Epithelial-to-Mesenchymal Transition and Oncogenic Ras Expression in Resistance to the Protein Kinase Cβ Inhibitor Enzastaurin in Colon Cancer Cells

Abstract: Identifying molecular factors of sensitivity and resistance of cancer cells to enzastaurin, a drug inhibiting protein kinase C (PKC) β, remains a major challenge to improve its clinical development. Investigating the cellular effects of enzastaurin in a panel of 20 human cancer cell lines, we found that most cells displaying oncogenic K-Ras mutations also display resistance to enzastaurin. Wild-type (WT) K-Ras cancer cells displaying high sensitivity to enzastaurin also expressed high mRNA levels of epithelial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 33 publications
(57 reference statements)
2
29
0
Order By: Relevance
“…EMT provides cells the ability to migrate and invade, and reflects the plasticity of epithelial cells [28]. While epithelial cells undergo EMT, they acquire a mesenchymal phenotype, including decreased cell-cell adherent junctions and increased motility and chemotherapeutic resistance [28].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…EMT provides cells the ability to migrate and invade, and reflects the plasticity of epithelial cells [28]. While epithelial cells undergo EMT, they acquire a mesenchymal phenotype, including decreased cell-cell adherent junctions and increased motility and chemotherapeutic resistance [28].…”
Section: Introductionmentioning
confidence: 99%
“…EMT provides cells the ability to migrate and invade, and reflects the plasticity of epithelial cells [28]. While epithelial cells undergo EMT, they acquire a mesenchymal phenotype, including decreased cell-cell adherent junctions and increased motility and chemotherapeutic resistance [28]. It has been reported that EMT is involved in the progression of carcinomas of different sites including colon, head and neck, pancreas, liver, esophagus and lung [29][30][31][32][33][34][35][36][37].…”
Section: Introductionmentioning
confidence: 99%
“…The Colo205-R cell line was derived from Colo205 cells with an acquired resistance to protein kinase C modulators like Enzastaurin (LY317615-HCI, Eli Lilly) [16, 21]. SQ20B-R cells were derived from inherent radio-resistant SQ20B head & neck squamous cancer cells with acquired resistance to PTX008 that developed after about 6 months of treatment.…”
Section: Resultsmentioning
confidence: 99%
“…Likewise, high expression of FAP has also been described to lead to poor patient prognosis17. Oncogenic K-RAS was associated with transcription of the antiapoptotic GADD45B18. However, no direct correlation between survival and GADD45B expression in colon cancer has been described earlier.…”
Section: Discussionmentioning
confidence: 99%